Addition of biochar into activated sludge improves removal of antibiotic ciprofloxacin. (February 2020) - Kim, Do Gun; Choi, Donggeon; Cheon, Seungyong; Ko, Seok-Oh; Kang, Seoktae; Oh, Seungdae
Abstract: This study evaluated the effectiveness of treating a ciprofloxacin (CIP)-containing waste stream by activated sludge dosed with apple-tree-derived biochar (AB). AB was dosed to activated sludge-inoculated bioreactors with varied AB volume ratios (10 %, 20 %, and 40 % of AB to the total volume). The AB-dosed bioreactors were operated by feeding by 1 mg L −1 of CIP. At steady state, the AB-dosed bioreactors achieved significantly enhanced CIP removal (up to 94 %) and the removal efficiency was positively correlated with the AB volume ratio, suggesting the key role of AB on controlling the removal efficiency of AB. The CIP removals occurring in the bioreactors at steady state were largely through adsorption to AB. This work further carried out systematic assessment on the adsorption kinetics, isotherm, and characteristics of CIP on AB in variable environmental conditions. CIP adsorption onto AB was controlled by diffusion in macropores, π-π electron-donor-acceptor interactions, and electrostatic attraction. Our results suggested that hardwood-derived biochar may be a promising bio-waste additive for improving micropollutant removals in activated sludge processes, which has implications on further devising a simple and cost-effective treatment option for antibiotics-bearing waste streams.